Bleeding outcomes and factor utilization after switching to an extended half-life product for prophylaxis in haemophilia A in Austria - Ay, Cihan (Sci Rep, 2021)
To prevent bleeding in severe haemophilia A [SHA, defined as factor VIII (FVIII) activity < 1%] regular prophylactic FVIII replacement therapy is required, and the benefits of factor products with extended half-life (EHL) over traditional standard half-life (SHL) are still being debated. We performed a multi-centre, retrospective cohort study of persons with SHA in Austria aiming to compare clinical outcomes and factor utilization in patients with SHA, who switched from prophylaxis with SHL to an EHL. Data were collected from haemophilia-specific patient diaries and medical records. Twenty male persons with SHA (median age: 32.5 years) were included. The most common reason for switching to the EHL was a high bleeding rate with SHL. Switch to rFVIII-Fc resulted in a significantly decreased annualized bleeding rate (ABR; median difference (IQR): − 0.3 (− 4.5–0); Wilcoxon signed-rank test for matched pairs: Z = − 2.7, p = 0.008) and number of prophylactic infusions per week (− 0.75 (− 1.0–0.0); Z = − 2.7, p = 0.007). Factor utilization was comparable to prior prophylaxis with SHL (0.0 (− 15.8–24.8) IU/kg/week; Z = − 0.4, p = 0.691). In summary, switch to EHL (rFVIII-Fc) was associated with an improved clinical outcome, reflected by ABR reduction, and less frequent infusions, without significantly higher factor usage.